Mitral valve annulus and circumflex artery: In vivo study of anatomical zonesCentral MessagePerspective - Vincenzo Caruso, MD; Usman Shah, FRCS (CTh); Haytham Sabry, FRCS (CTh); Inderpaul Birdi, FRCS (CTh) (JTCVS Techniques)
Objective: To provide, with the use of preoperative coronary computed tomography angiography, an in vivo anatomical characterization of the relationship between the circumflex artery and mitral valve annulus to identify different risk classes and to increase the surgical awareness of those anatomical relations. Methods: Ninety-five (mean age: 64.2 ± 11.7) consecutive patients, initially referred for elective minimally invasive mitral valve surgery, underwent preoperative coronary computed tomography angiography. The distance between the circumflex artery and mitral annulus was assessed using 6 points designed on the posterior mitral annulus, starting from the anterolateral to the posteromedial commissure; this design created an ideal 5-zone system. High-risk anatomy was defined as a distance less than 3 mm between the circumflex artery and the mitral valve annulus. Results: The shortest distance between the circumflex artery and mitral valve annulus was observed at the area between the anterolateral commissure and the midpoint of P1 scallop, so-called zone 1 (5.49 ± 3.13 mm), whereas the longest distance occurred at zone 5 (12.03 ± 4.93). Twenty-four patients (25%) were identified with high-risk anatomy (mean distance 1.94 ± 0.8 mm). Left dominant and co-dominant hearts demonstrated a shorter circumflex artery–mitral valve annulus distance at all the zones. At multinomial logistic regression, the pattern of coronary dominance and the size of the circumflex artery were independent factors for high-risk anatomy. Conclusions: Coronary computed tomography angiography is a useful investigation to identify patients at risk of circumflex artery flow disturbance; for high-risk anatomy, this knowledge may enhance a safer operative technique.